RANCANGAN SISTEM PENILAIAN KESELAMATAN PENGUNJUNG TEMPAT WISATA - Yudistira, IG.A. Anom; Susanto, Nur Agus (MAJALAH ILMIAH WIDYA, 2012)
Tourism is currently growing rapidly and is a necessity for people pleasure. However this activity is not immune from risk. Theresearch aims to discuss the design of the assestment system of safety for tourist sites. The method used surveys and documentsanalysis through focus group discussion. The results shows 10 indicators along with 29 parameters that can be seen on tables. Scoringresults according to the indicators and parameters are used to classify the tourist sites based on visitors safety risks.